2005
DOI: 10.1111/j.1365-2893.2005.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute hepatitis C infection in HIV‐infected patients: a retrospective analysis of eleven cases

Abstract: Studies on hepatitis C virus (HCV) monoinfected patients suggest high sustained treatment response rates of up to 98% when interferon monotherapy is administered during the acute phase of HCV-infection. To clarify whether early treatment of acute hepatitis C is similarly efficient in human immunodeficiency virus (HIV) positive patients, we conducted a retrospective survey of HIV-positive patients with acute HCV infection. Eleven HIV-positive patients who had been treated with interferon or interferon/ribavirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 10 publications
(15 reference statements)
1
28
1
1
Order By: Relevance
“…The first studies to identify this problem were from Northern Europe, specifically England, France, Germany, and The Netherlands in 2004 and 2005 [7-9, 10•, 11,12]. They reported clusters of new HCV infections in HIV-infected MSM and suggested that transmission could be linked to high-risk sexual and drug-use behaviors.…”
Section: Epidemic Of Hcv Infection In Hiv-infected Msm In Northern Eumentioning
confidence: 97%
See 1 more Smart Citation
“…The first studies to identify this problem were from Northern Europe, specifically England, France, Germany, and The Netherlands in 2004 and 2005 [7-9, 10•, 11,12]. They reported clusters of new HCV infections in HIV-infected MSM and suggested that transmission could be linked to high-risk sexual and drug-use behaviors.…”
Section: Epidemic Of Hcv Infection In Hiv-infected Msm In Northern Eumentioning
confidence: 97%
“…The earliest published studies of treatment of new HCV infection in HIV-infected MSM were retrospective, the treatment regimens were not standardized (ranging from IFN monotherapy to pegylated IFN and ribavirin [pIFN + RBV] from 24 to 48 weeks), and there was a wide range of sustained virologic response (SVR) rates, from 0% to 91% [8,12,14,20] (Table 1). Prospective studies followed quickly that were similar to each other in allowing time (typically 12 weeks from diagnosis) for spontaneous clearance to occur, and then most patients who did not spontaneously clear were treated with a combination of pIFN + RBV for 24 weeks [10,13,15] (Table 1).…”
Section: Treatmentmentioning
confidence: 99%
“…However, better response rates were reported among 11 acutely infected German patients, with 10 having SVR. 131 Ten patients with genotype 4 HCV and HIV were treated in France following a suspected common source sexually transmitted infection cluster. Treatment was provided within a mean time of 49 days from the onset of acute hepatitis, and a variety of interferon-based regimens were used.…”
Section: Treatment Of Acute Hcv Infectionmentioning
confidence: 99%
“…[2][3][4] In the UK in 2008 the Health Protection Agency set up an enhanced surveillance of recently acquired HCV. 5 Data were collected prospectively (January 2008 -March 2010) from 22 UK sites in London and the south-east.…”
Section: The Start Of the Epidemicmentioning
confidence: 99%